ナンキョク ショウワキチ ニオケル ジシン ケンチリツ - 金尾, 政紀; カナオ, マサキ; 神沼, 克伊; カミヌマ, カツタダ; Kanao, Masaki; Kaminuma, Katsutada (1995)
P(論文) 昭和基地(69.0°S, 39.6°E)では, 1967年より短周期, 長周期各3成分のアナログ記録による地震記象の読み取り作業が開始された。越冬の地球物理定常隊員により観測の保守がなされ, 着震時の読み取り作業が現在まで継続して行われている。験震した走時と震源のデータは, アメリカ地質調査所(USGS)と国際地震センター(ISC)に定期的に送られると共に, 極地研究所で再験震を行い"JARE Data Reports (Seismology)"として発刊されている。近年, エレクトロニクス技術の進歩によりモニター記録の質が向上すると共に, 同一の基準で再験震がなされた。本稿では, 1987年より1993年の7年間における験震データを用いて, 昭和基地で記録される地震の空間分布と時間的推移を詳しく調べ, またISCデータを用いた結果と比較することで昭和基地の地震検知率について考察した。 Phase readings of teleseismic earthquakes at Syowa Station (69.0°S, 39.6°E), Antarctica have been carried out since 1967 by use of analog records of three-component short-and long-period seismometers. Seismic observations and phase readings have been conducted by the wintering members for geophysics of the Japanese Antarctic Research Expedition (JARE). The arrival times of P-waves have been reported to the United States Geological Survey (USGS) and the International Seismological Center (ISC), then published as the "JARE Data Reports (Seismology)" by the National Institute of Polar Research (NIPR). In recent years, the quality of chart records has been improved by the advance of electronics. In this paper, the hypocentral distribution of the detected earthquakes for the seven year period from 1987 to 1993 was presented and the spatial distribution and time variations for epicental parameters were investigated. Moreover, the detection capability of earthquakes was discussed in relation to the report from ISC data. departmental bulletin paper